ACCOUNTING-BASED BUSINESS PLAN DEVELOPMENT: COST ANALYSIS, FINANCIAL STATEMENT PROJECTION, AND PROFITABILITY IMPROVEMENT STRATEGIES FOR MSME TARA’S PROMOTIONAL BAGS (INTERNATIONAL SEMINAR, 2026)
This study aims to develop an accounting-based business plan for Tara’s Promotional Bags, a micro, small, and medium enterprise (MSME) engaged in the production of promotional bags. The research focuses on integrating cost analysis, financial statement projections, and profitability enhancement strategies as the foundation for effective business planning. A descriptive qualitative approach was employed, combining observation, interviews, and documentation techniques to obtain comprehensive financial and operational data. The cost analysis identifies the structure of production expenses and highlights potential cost efficiency opportunities. Financial projections were prepared to illustrate expected income, balance sheet positions, and cash flow performance over a one-year period, providing a realistic overview of the enterprise’s financial prospects. Furthermore, profitability strategies were formulated by emphasizing cost control, pricing adjustments, and product diversification to enhance competitiveness. The results indicate that applying accounting principles in business planning not only improves financial management accuracy but also supports decision-making processes for sustainable growth. The proposed business plan can serve as a practical model for similar MSMEs seeking to strengthen financial performance through structured accounting-based management.